Bacterial diversity in the sediments of three lagoons in Central Vietnam - Thi Hong, Tran; Viet Cuong, Pham; Van Phuong, Nguyen (Academia Journal of Biology, 2023)
The prokaryotic community in sediment plays an important role in the nutrient cycles of lagoon ecosystems. However, the diversity of microbiota in sediments of Vietnamese lagoons has not been discovered. In this study, sediment samples from three lagoons in Central Vietnam were collected. The microbial community structure in the sediments was determined using Illumina sequencing of 16S rRNA at V3V4 regions. Mother software was used to analyze the data and identify the Operational Taxonomic Units (OTUs). Proteobacteria, Firmicutes, Campilobacterota, and Bacteroidetes were the major phyla in three lagoons, while Fusobacteria, Verrucomicrobia, Acidobacteria, Actinobacteria, and Chloroflexi were the minor. These groups of bacteria have been reported to be involved in organic metabolism cycles in sediments. Tam Giang lagoon showed more diversity in species composition when compared with Nai and Thi Nai lagoons. Class Clostridia were predominant in Tam Giang sediment (46%), which may indicate the presence of organic sewage in the environment. Thi Nai and Nai lagoons witnessed the significant presence of Lactobacilales and Vibrionales. While Vibrionales is an indicator of urban pollution, Lactobacilales and other groups of phylum Actinobacteria were potential materials for the screening of natural antibiotics.